Across-country dairy breeding strategies in sub-Saharan Africa - Opoola, Oluyinka (The University of Edinburgh, 2019)
Genetic improvement of livestock has a major impact on animal productivity and its effects are permanent, cumulative and usually highly cost effective. It is also of considerable potential value in countries, mostly in need of increased food supply and security like those in sub-Saharan Africa. However, genetic improvement has not been carried out systematically in most sub-Saharan Africa countries. This is in part because of lack of animal performance recording, insufficient infrastructure, small herd sizes and limited pedigree information. Most genetic improvement initiatives in dairy cattle have often relied on importation of foreign (exotic) breeds. Only a few countries such as South Africa and Kenya have been collecting dairy performance data for national genetic evaluations for some time. Initiatives such as the African Dairy Genetic Gains Programme are helping other countries such as; Tanzania and Ethiopia to develop animal recording systems which will start to provide pre-requisite data for genetic evaluations. Improvements in data recording in multiple countries present an opportunity to develop new approaches to dairy improvement and across-country genetic evaluations. Across-country genetic evaluations would facilitate selection decisions and underpin the fledgling breeding programmes in these countries. Elsewhere, pooling and jointly analysing data across different countries, where common sires are been used, has resulted in more accurate genetic evaluations than using within-country data only. The hypothesis in the present study was that across-country genetic evaluation of dairy cattle in sub-Saharan Africa would result in accurate genetic parameters and estimated breeding values hence, improve genetic progress. In order to test this hypothesis, four objectives were addressed as follows. Firstly, a survey was conducted to investigate the current status and needs of the dairy improvement sector in sub-Saharan Africa. Secondly, existing animal data collated from three countries (Kenya, South Africa and Zimbabwe) from Holstein- Friesian and Jersey breeds were used to determine the level of connectedness among the respective dairy populations. Thirdly, estimates of genetic parameters and breeding values for milk production and fertility traits were derived within and across these countries. Fourthly, the potential genetic gains that could arise from within and across-country genetic selection were estimated. Results from the survey indicated that the main respondent’s challenges in sub- Saharan Africa dairy production systems are; poor animal recording, poorly defined animal genetic improvement goals and strategies, inadequate dairy marketing structure and scarce human capacity. The survey identified close collaborations as one of the mitigation measures to these challenges. Results from production and pedigree data for the three countries showed that there were strong links and connectedness in both breeds. Genetic parameter estimation indicated that all three populations would benefit from joint genetic analyses in terms of improved accuracy of estimates. For example, in Holstein-Friesians, heritability (h2) for 305-day milk yield in five lactations (305D MY) across the three countries was 0.11 (s.e=0.014). Within country, estimates for South Africa and Zimbabwe were 0.12 (s.e=0.018) and 0.10 (s.e=0.025), respectively, whereas it was not significantly different from zero for Kenya. In fact in several cases, within-country parameter estimates were either not significantly different from zero or non-estimable. Genetic parameters were always estimable in across-country analyses. In terms of expected genetic progress, the results showed that all three countries would benefit from genetic progress generated from selection in an across country initiative. For production traits, Kenya benefited the most (100% increase in genetic gain from across-country compared to within-country selection) than Zimbabwe (55- 73% increase over within-country) and lowest benefits for South Africa (2-28%). For reproduction traits, Kenya again benefitted the most (100%), as compared to Zimbabwe (59-100%) and South Africa (16-69%). The study suggests that, in general, joint genetic evaluations may support breeding programmes by providing more accurate genetic parameters and estimated breeding values than national initiatives. Furthermore, an across-country breeding programme based on a joint genetic evaluation could provide a platform for shared genetic progress. Such a programme would offer a wider choice of animals for selection than national evaluations. This type of across-country collaboration would facilitate animal trade between countries in terms of both exportations and importations, and would also address some of the key needs identified in the stakeholder survey.
Keywords: sub-Saharan Africa; genetic improvement initiatives; dairy improvement infrastructure; genetic parameters; genetic evaluations; Holstein-Friesian; Jersey